The social status of vocational education and training in Switzerland: Information brochure for professionals in vocational education and training - Thomas Bolli; Ladina Rageth; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2018)
The Swiss vocational education and training (VET) system is held in high regard by other countries. Young skilled workers from Switzerland consistently secure top marks at world skills competitions. But how has the social status of VET developed relative to that of baccalaureate schools? What changes can be ascertained in the various parts of the country and population groups? We have been able to answer these and other questions thanks to a new measurement.
Keywords: 330